Simulation of a new neutron filter with average energy 1.6 keV - V. A. Libman; O. O. Gritzay (Ядерна фізика та енергетика)
A new interference neutron filter with an average energy of 1.65 keV was modeled based on the latest version of the evaluated nuclear data library ENDF/B VIII.0. The main components of the filter: scandium, nickel-60, iron-54, and selenium-80. We expect the following characteristics of this new filter: the average energy 1.6 keV, the mainline FWHM 0.7 keV, purity of the mainline 97 %, the neutron flux density 1.0·106 n·s-1·cm-2. Experimental verification of the new filter parameters is planned during the next campaign of the WWR-M reactor.